2010
DOI: 10.1039/c0cc00827c
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric and catalytic Sn-mediated dehydrocoupling of primary phosphines

Abstract: The room-temperature reactions of stannocene, Cp*(2)Sn, with a range of primary phosphines, RPH(2), result in diphosphanes [RP(H)P(H)R]. The reactions involving Cp*(2)SnCl(2), however, result in catalytic dehydrocoupling; the first example of main group metal catalysed dehydrocoupling to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 24 publications
0
24
0
3
Order By: Relevance
“…Though zinc complexes would not be expected to demonstrate the same kinds of reactivity as formally d 8 and d 0 metal complexes, which are demonstrated phosphine dehydrocoupling catalysts [8], the recent report of a tin complex, Cp* 2 SnCl 2 , that is a catalyst for dehydrocoupling prompts the study of alternative metal species [14].…”
Section: Introductionmentioning
confidence: 99%
“…Though zinc complexes would not be expected to demonstrate the same kinds of reactivity as formally d 8 and d 0 metal complexes, which are demonstrated phosphine dehydrocoupling catalysts [8], the recent report of a tin complex, Cp* 2 SnCl 2 , that is a catalyst for dehydrocoupling prompts the study of alternative metal species [14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this reaction requires the tin(IV) precursor. Reaction of decamethylstannocene with the same phosphine substrates gave diphosphine but only stoichiometrically at a 2:1 phosphine:tin ratio [84]. This initial result suggests that a new area of main-group element catalyzed dehydrocoupling is possible.…”
Section: B Main-group Catalystsmentioning
confidence: 92%
“…Wright and coworkers have recently made a significant breakthrough in this regard with the report of organotin complexes as catalysts for the dehydrocoupling of phosphines [84]. In particular, it was found that decamethylstannocene dichloride (Cp* 2 SnCl 2 ) dehydrocoupled primary phosphines, RPH 2 , where R = t Bu, Cy, or ferrocenyl (Fc) to predominately the diphosphine product with some formation of the four-and five-membered rings (eq.…”
Section: B Main-group Catalystsmentioning
confidence: 98%
“…[9] More recently, main-group reagents such as [Sn (C 5 Me 5 ) 2 Cl 2 ] have been reported to be suitable catalysts for PÀP bond formation, although with modest TON values. [10] Detailed mechanistic information on the dehydrocoupling of phosphanes only exists in a few cases, mainly concerning early transitionmetal catalysts.…”
Section: In Memory Of María Pilar Garcíamentioning
confidence: 99%
“…[9] More recently, main-group reagents such as [Sn (C 5 Me 5 ) 2 Cl 2 ] have been reported to be suitable catalysts for PÀP bond formation, although with modest TON values. [10] Detailed mechanistic information on the dehydrocoupling of phosphanes only exists in a few cases, mainly concerning early transitionmetal catalysts. [2b, 11] Nonetheless, the Rh V diphosphanide species [Rh (C 5 Me 5 )(H) 2 (PR 2 ) 2 ] was tentatively hypothesized by Bçhm and Brookhart to mediate in the dehydrocoupling of secondary phosphanes, [9b] while [Rh(dippe)(CH 2 Ph)(H)-(PHPh)] (dippe = iPr 2 PCH 2 CH 2 PiPr 2 ) was observed as a transient species in the preparation of the dinuclear complex [{Rh(m-PHPh)(dippe)} 2 ] as a precatalyst for dehydrocoupling primary phosphanes.…”
mentioning
confidence: 99%